Sofosbuvir‐containing regimens are safe and effective in the treatment of HCV patients with moderate to severe renal impairment. (20th December 2019) - Eletreby, Rasha; El‐Serafy, Magdy; Anees, Mahmoud; Kasem, Gamal; Salama, Marwa; Elkhouly, Reham; Hamdy, Mostafa; Abdel Haleem, Hisham; Kamal, Ehab; Abdel‐Razek, Wael; Salama, Rabab; Elshenawy, Mohamed; et al.
Abstract: Background and Aims: This study aimed to assess the safety and efficacy of sofosbuvir (SOF)‐based regimens in patients with moderate to severe renal impairment; a subject which has been questioned by many investigators with conflicting results. Methods: This is a real‐life multicentre retrospective cohort study on 4944 chronic Hepatitis C virus (HCV) patients with chronic kidney disease (CKD) (eGFR <60 mL/min/1.73 m 2 ) who received SOF‐based therapy in specialized treatment centres affiliated to the National Committee for the Control of Viral Hepatitis in Egypt. The efficacy and safety of SOF‐based regimens was assessed. Results: Week 12 virological response rates were 97.5%, 96.7%, 85.7% and 80% in the total cohort, patients with eGFR <30 mL/min/1.73 m 2, patients with associated hepatic decompensation and patients on dialysis respectively. Various treatment regimens did not statistically affect the response rates. Treatment experience, cirrhosis and diabetes were predictors of treatment failure on multivariate analysis. Serious adverse events occurred in 0.1% of cases. Forty patients (0.8%) discontinued treatment. Conclusion: Sofosbuvir‐based regimens are effective and safe for treating patients with chronic HCV and moderate to severe CKD, and in those with associated hepatic decompensation.